2020
DOI: 10.1186/s12889-020-09650-0
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental risk factors for the accidental drowning of children under five in China

Abstract: Background Accidental drowning of children under five is a serious problem in China. The present study analyzed data on environmental and sociodemographic factors and on primary caregivers of drowned children to understand factors that may contribute to this problem. Methods The present study collected information on 563 cases of drowning in children under five from October 1, 2015, to September 30, 2016, in 334 sampling districts in China. Primary caregivers were interviewed individually using the Drowning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
3
10
1
Order By: Relevance
“…In this study children were in the high-risk group, and the highest frequency referred to two-year-old children. Almost similar results were found in a study held in Ireland by Davey et al showed that the majority of drowning cases affected children between the ages of 1-4 ( 8 ), other studies held by Evans et al ( 9 ), Denny et al ( 10 ), Wang et al ( 11 ), and Raess et al ( 12 ) showed that drowning mostly affected children under the age of 5 which comes in agreement with our findings. This result may have been caused by the absence of children strict supervision.…”
Section: Discussionsupporting
confidence: 93%
“…In this study children were in the high-risk group, and the highest frequency referred to two-year-old children. Almost similar results were found in a study held in Ireland by Davey et al showed that the majority of drowning cases affected children between the ages of 1-4 ( 8 ), other studies held by Evans et al ( 9 ), Denny et al ( 10 ), Wang et al ( 11 ), and Raess et al ( 12 ) showed that drowning mostly affected children under the age of 5 which comes in agreement with our findings. This result may have been caused by the absence of children strict supervision.…”
Section: Discussionsupporting
confidence: 93%
“…But the result of this study doesn't nd statistically signi cant evidence (OR: 1.111, 95%CI: 0.956 ~ 1.291). This may attributed to the reason that the resolution of our data is too large to nd meaningful results, the drowning incidents usually occurred within 100 meters of a body of water (Wang, et al, 2020), but the resolution of our data (i.e. population density) is 1kilometer, the distance is too long for children to nd a natural water body.…”
Section: Discussionmentioning
confidence: 91%
“…1988). In addition, safety and rst aid education in urban is more adequate than rural place, 83.1% of rural residents had no knowledge of rst aid skills for drowning (Wang, et al, 2020). Western China with lower per capita income has a higher drowning mortality although some western provinces are not so hot and rainy.…”
Section: Discussionmentioning
confidence: 99%
“…Drowning primarily occurred in ponds, canals, rivers and wells, and over 90% of those bodies of waters had no safety measures. Almost 90% of primary caregivers did not provide full‐time care for the children, and 80% had no knowledge of first aid skills for resuscitation 2 …”
mentioning
confidence: 99%
“…Almost 90% of primary caregivers did not provide full‐time care for the children, and 80% had no knowledge of first aid skills for resuscitation. 2 …”
mentioning
confidence: 99%